Dual-polarized angle selective surface - Lou, Zhe (Nanyang Technological University, 2022)
Angle selective surface (ASS) is the surface that allows incident electromagnetic waves with certain incident angle to transmit with low insertion loss and prevents waves with other angles from passing. Four types of dual-polarized angle selective surfaces, consisting of 2, 3 and 4 layers of two-dimensional frequency selective surfaces, respectively, are proposed in this thesis. Simulations of these structure are conducted with the help of ANSYS HFSS for verification. Two basic structures consisting of 2 single layer FSSs show angular selectivity with high transmission at incident angle smaller than a certain transmission threshold angle and low transmission at incident angle larger than a certain reflection threshold angle at a narrow band in X-band and Ku-band, respectively. Additional layers in 3- and 4-layer structure extend this narrow band, while not degrading the angular selectivity as well as the polarization independency. Key words: Angle selective surface, frequency selective surface, dual-polarized.